Curing of an Escherichia coli Episome by Rifampicin - Bazzicalupo, Paolo (1972)
Low doses of rifampicin, an antibiotic that specifically inhibits RNA polymerase, cure F(+) cells from the episome. An E. coli mutant, whose RNA polymerase is resistant to rifampicin, does not show the curing. The growth of Hfr strains, which replicate the chromosome by the F-replication system, is inhibited by low doses of the antibiotic.